Deep-level impurities hyperdoped diamond: a first-principles calculations. (6th January 2021) - Dong, Xiao; Wang, Tianxing; An, Yipeng; Wang, Yongyong
Abstract: A hyperdoped diamond material is engineered by first-principles calculations in this work. Several deep-level elements, such as S, Se, Te, Co, Au, V, Ni, are chosen as dopants in the diamond. The formation energy results show that the substitutional configuration of the dopants is more stable than the interstitial ones. The substitutional configurations of chalcogen dopants (S, Se, Te) can introduce a nearly filled intermediate band (IB) in the upper half of the bandgap of the diamond. The substitutional configurations of several transition metals, such as Co, Au, V, Ni, and Cu, can form partially filled IB(s) near the center of the bandgap, which is more appropriate than that formed by the chalcogens. The dielectric function results indicate that all of these deep-level elements can lead to the sub-bandgap absorption and the absorption range and intensity vary dramatically with different dopants. Among these dopants, Co, Au, and Cu exhibit a special strong sub-bandgap absorption in a longer wavelength range, which would make the material to be an excellent photoelectric device. With reducing the concentration of the transition metal dopants, the IBs in the bandgap are narrower and tend to separate from each other and the sub-bandgap absorptions reduce sharply. Our conclusions imply that the photoelectric properties of the novel diamond material would be modulated by changing the dopant types and concentrations.